2011
DOI: 10.1126/science.1198973
|View full text |Cite|
|
Sign up to set email alerts
|

Adipose Triglyceride Lipase Contributes to Cancer-Associated Cachexia

Abstract: Cachexia is a multifactorial wasting syndrome most common in patients with cancer that is characterized by the uncontrolled loss of adipose and muscle mass. We show that the inhibition of lipolysis through genetic ablation of adipose triglyceride lipase (Atgl) or hormone-sensitive lipase (Hsl) ameliorates certain features of cancer-associated cachexia (CAC). In wild-type C57BL/6 mice, the injection of Lewis lung carcinoma or B16 melanoma cells causes tumor growth, loss of white adipose tissue (WAT), and a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
484
7
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 498 publications
(534 citation statements)
references
References 30 publications
29
484
7
6
Order By: Relevance
“…However, lipolysis and lipid wasting may occur to an extent before muscle loss. 63 Additionally, studies in a mouse model of colon cancer demonstrated an increase in protein kinase-A-mediated lipolysis in early stage cachexia, 65 and this ''early'' lipolysis was implicated in (1) the inception of a negative energy balance that worsens over the course of CAC progression, and (2) a direct loss of skeletal muscle. 66 Lipolysis results in increased free fatty acids in circulation, which then get taken up by skeletal muscle; the excess of intramuscular free fatty acids results in several biochemical changes, such as the expression of ubiquitin lipases Atrogin-1 and MuRF 67 that lead to skeletal muscle atrophy.…”
Section: Adipose Tissue Contributions To Cac Lipolysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, lipolysis and lipid wasting may occur to an extent before muscle loss. 63 Additionally, studies in a mouse model of colon cancer demonstrated an increase in protein kinase-A-mediated lipolysis in early stage cachexia, 65 and this ''early'' lipolysis was implicated in (1) the inception of a negative energy balance that worsens over the course of CAC progression, and (2) a direct loss of skeletal muscle. 66 Lipolysis results in increased free fatty acids in circulation, which then get taken up by skeletal muscle; the excess of intramuscular free fatty acids results in several biochemical changes, such as the expression of ubiquitin lipases Atrogin-1 and MuRF 67 that lead to skeletal muscle atrophy.…”
Section: Adipose Tissue Contributions To Cac Lipolysismentioning
confidence: 99%
“…61,62 The importance of lipolysis in CAC was demonstrated in a study that showed that the inhibition of lipid mobilization can improve the CAC state. 63 A murine model of animals implanted with murine adenocarcinoma 16 (MAC16) tumors reported changes in adipose tissue that included shrunken adipocytes and decreased expression of adipose tissue transcription factors. 64 From a clinical perspective, a critical component of the body mass loss observed in CAC is the depletion of muscle mass, which usually precedes the observation of significant changes in adipose tissue mass and is associated with decrease in muscle function and mobility.…”
Section: Adipose Tissue Contributions To Cac Lipolysismentioning
confidence: 99%
“…Indeed, many years ago Argilés and coworkers (2005) proposed the existence of a cross talk between the two tissue compartments. Such hypothesis has been clearly demonstrated in a recent report (Das et al, 2011), showing that inhibition of lipolysis in tumor-bearing mice by genetic ablation of lipolytic enzymes prevents hyperlipidemia and adipose mass depletion, but also skeletal muscle wasting.…”
Section: Body and Tissue Wastingmentioning
confidence: 71%
“…In cancer patients, in particular, lipase expression is inversely correlated with body mass index (see Bing, 2011). Finally, genetic manipulations aimed at deleting each of the two lipases result in restoration of normal adipose tissue mass in tumor-bearing mice (Das et al, 2011;see above). Lipolysis-derived fatty acids, through the action of the adipocyte-specific gene cell death-inducing DNA fragmentation factor-[alpha]-like effector A (CIDEA), may serve as substrates for energy production through oxidation (Laurencikiene et al, 2008).…”
Section: Tissue Wasting In Cachexia: Hypoanabolism or Hypercatabolism?mentioning
confidence: 99%
See 1 more Smart Citation